On Harold J. Berman’s (revolutionary) Hypothesis – law and science in the Middle Ages - Leszczyński, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
In his book “Law & Revolution” Harold J. Berman ventures an opinion that certain sociopolitical transformations of XIth and XIIth century had a formative character for subsequent Western history. Emerging profession of lawyer (decretists) played a fundamental role in that upheaval, called by Berman a revolution. Moreover, Berman is trying to connote that with the creation of universities and, more generally, modern science. In my article I will try to investigate different meanings of revolution in Berman’s argument and its general structure.